A New Perspective on Earnings Management in Emerging European Countries: Investigation on Environmental Factors that Explain Differences in Earnings Management - Callao, Susana; Jarne, José I.; Wróblewski, David (Journal of Accounting, Business and Finance Research, 2019)
This paper presents a new perspective on earnings management analyzing and comparing emerging European countries in the presence of environmental factors of developing countries. We provide empirical evidence on differences in the extent of earnings management across countries. Developing Eastern European countries experienced important changes. They have been in transition over the past decade, and remain making great strides to overcome the drag exerted by their communist heritage. Nevertheless, the studies on earnings management based on emerging economies are rare and hardly pursued due to the presence of institutional and regulatory differences between developed and emerging economies. Therefore, the present study fulfils the important gap in earnings management literature related to developing countries. Our results confirm that managers from different emerging European countries manage earnings differently. Additionally, we identify that there is not a sole reason affecting the managers’ decisions, but a significant number of circumstances and characteristics. Whether a firm’s environment offers more protection or is characterized by a higher level of development, higher foreign investments, it helps to limit the earnings management. In addition, when accounting and tax are not as strongly aligned with market approach as expected, it also limits the earnings management behaviour of managers.